ENDCELL-Seud: a Delphi protocol to harmonise methods in endometrial cell culturing - Andrea Romano; Sun-Wei Guo; Jan Brosens; Asgerally Fazlebas; Caroline E Gargett; Stefan Giselbrecht; Martin Gotte; Linda Griffith; Hugh S Taylor; Robert N Taylor; Hugo Vankelecom; Charles Chapron; et al. (Bioscientifica, 2022)
In vitro culturing of endometrial cells obtained from the uterine mucosa or ectopic sites is used to study molecular and cellular signalling relevant to physiologic and pathologic reproductive conditions. However, the lack of consensus on standard operating procedures for deriving, characterising and maintaining primary cells in two- or three-dimensional cultures from eutopic or ectopic endometrium may be hindering progress in this area of research. Guidance for unbiased in vitro research methodologies in the field of reproductive science remains essential to increase confidence in the reliability of in vitro models. We present herein the protocol for a Delphi process to develop a consensus on in vitro methodologies using endometrial cells (ENDCELL-Seud Project). A steering committee composed of leading scientists will select critical methodologies, topics and items that need to be harmonised and that will be included in a survey. An enlarged panel of experts (ENDCELL-Seud Working Group) will be invited to participate in the survey and provide their ratings to the items to be harmonised. According to Delphi, an iterative investigation method will be adopted. Recommended measures will be finalised by the steering committee. The study received full ethical approval from the Ethical Committee of the Maastricht University (ref. FHML-REC/2021/103). The study findings will be available in both peer-reviewed articles and will also be disseminated to appropriate audiences at relevant conferences.